The extent of the banks' duty in processing documentary credits in international trade - Karumazondo, Laurence (Department of Commercial Law, 2023)
Documentary credits, also called letters of credit or banker's commercial credits, are the most common system of payment in international trade and have been described as 'the life blood of international commerce'.